Sirtuin 2 Regulates Protein LactoylLys Modifications. (9th April 2021) - Jennings, Erin Q.; Ray, Jason D.; Zerio, Christopher J.; Trujillo, Marissa N.; McDonald, David M.; Chapman, Eli; Spiegel, David A.; Galligan, James J.
Abstract: Post‐translational modifications (PTMs) play roles in both physiological and pathophysiological processes through the regulation of enzyme structure and function. We recently identified a novel PTM, lactoylLys, derived through a nonenzymatic mechanism from the glycolytic by‐product, lactoylglutathione. Under physiologic scenarios, glyoxalase 2 prevents the accumulation of lactoylglutathione and thus lactoylLys modifications. What dictates the site‐specificity and abundance of lactoylLys PTMs, however, remains unknown. Here, we report sirtuin 2 as a lactoylLys eraser. Using chemical biology and CRISPR‐Cas9, we show that SIRT2 controls the abundance of this PTM both globally and on chromatin. These results address a major gap in our understanding of how nonenzymatic PTMs are regulated and controlled. Abstract : Protein post‐translational modifications (PTMs) alter the structure and function of enzymes and are often regulated by enzymatic removal by "erasers". The nonenzymatically derived PTM lactoylLys was recently identified in states of elevated glycolytic flux. Herein, we report the deacylase sirtuin 2 as the first known "eraser" for lactoylLys, expanding the knowledge of enzymatic regulation of nonenzymatically derived protein PTMs.